2009
DOI: 10.1007/s11262-009-0345-2
|View full text |Cite
|
Sign up to set email alerts
|

Mal de Río Cuarto virus (MRCV) genomic segment S3 codes for the major core capsid protein

Abstract: Mal de Río Cuarto virus (MRCV) is a newly described species of the genus Fijivirus, family Reoviridae. Compared with other plant-infecting genus of the family, the function and localization of MRCV and other Fijivirus proteins are poorly understood. Through analysis of viral particle purifications, we positively identified five structural proteins of approximately 170, 140, 130, 66, and 62 kDa. The protein encoded by MRCV S3 genomic segment was expressed as a fusion protein in Escherichia coli, purified and us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Interestingly, as it has been demonstrated for Rotavirus (Pesavento et al, 2006), the endoplasmic reticulum (ER) might play a role during MRCV, and possibly other fijiviruses, replication cycle (Maroniche et al, 2011). Sequence analysis of MRCV-encoded proteins, analysis of viral particle purifications and inmunogold labeling led to the identification of viral structural proteins such as a putative RNA-dependent RNA polymerase coded by S1 (P1) (Diste ´fano et al, 2003), a major core protein encoded by S3 (P3) (Diste ´fano et al, 2003(Diste ´fano et al, , 2009, a hypothetical guanylyltransferase encoded by S4 (P4) (Diste ´fano et al, 2002;Supyani et al, 2007), a protein with an ATP/GTP binding motif typical of helicases encoded by S8 (P8) (Diste ´fano et al, 2002) and a major outer capsid protein encoded by S10 (P10) (Diste ´fano et al, 2005). Our preliminary results also suggest that P4 is the B-spike protein (Diste ´fano, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, as it has been demonstrated for Rotavirus (Pesavento et al, 2006), the endoplasmic reticulum (ER) might play a role during MRCV, and possibly other fijiviruses, replication cycle (Maroniche et al, 2011). Sequence analysis of MRCV-encoded proteins, analysis of viral particle purifications and inmunogold labeling led to the identification of viral structural proteins such as a putative RNA-dependent RNA polymerase coded by S1 (P1) (Diste ´fano et al, 2003), a major core protein encoded by S3 (P3) (Diste ´fano et al, 2003(Diste ´fano et al, , 2009, a hypothetical guanylyltransferase encoded by S4 (P4) (Diste ´fano et al, 2002;Supyani et al, 2007), a protein with an ATP/GTP binding motif typical of helicases encoded by S8 (P8) (Diste ´fano et al, 2002) and a major outer capsid protein encoded by S10 (P10) (Diste ´fano et al, 2005). Our preliminary results also suggest that P4 is the B-spike protein (Diste ´fano, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…MRCV quantification was carried out by amplifying a fragment of MRCV segment S3 (MRCV-S3). Segment S3 codes for the major core capsid protein (Distéfano et al , 2009) and is the most conserved genomic segment (Distéfano et al , 2003). As internal control, the D. kuscheli ubiquitin gene (UBI) was amplified (Maroniche et al , 2011).…”
Section: Methodsmentioning
confidence: 99%
“…All known fi jiviruses contain ten linear genomic segments of double-stranded RNA (dsRNA), ranging in size from approximately 1.4 to 4.5 kb and named S1-10 according to their migration in PAGE, and most of them replicate in their plant hosts, where they induce growth abnormalities. Previous extensive studies have shown that the four viral pathogens of MRDD are closely related to each other and similar in particle morphology, genomic profi le, and serological relationships (Luisoni et al, 1973;Milne et al, 1973Milne et al, , 1977aReddy et al, 1975Reddy et al, , 1983Isogai et al, 1995;Zhang et al, 2001a,b;Distéfano et al, 2002Distéfano et al, , 2003Distéfano et al, , 2005Distéfano et al, , 2009Guzmán et al, 2007, Wang et al, 2010. All these viruses naturally infect maize and cause similar symptoms on maize or other host plants (Milne et al, 1977a;Attoui et al, 2012).…”
Section: Introductionmentioning
confidence: 97%